2017
DOI: 10.1186/s40644-017-0129-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and complications of endoscopic and percutaneous biliary drainage in malignant obstructive jaundice: a systematic review and meta-analysis

Abstract: BackgroundMalignant obstructive jaundice is a common problem in the clinic. Currently, the generally applied treatment methods are percutaneous transhepatic biliary drainage (PTBD) and endoscopic biliary drainage (EBD). Nevertheless, there has not been a uniform conclusion published on either efficacy of the two types of drainage or the incidence rate of complications. Therefore, we conducted a systematic review and meta-analysis of studies comparing endoscopic versus percutaneous biliary drainage in malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
3
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 17 publications
0
105
3
7
Order By: Relevance
“…The decrease in bilirubin levels also helps the body overcome the surgical stress. 27 Although the total length of hospital stay of patients with PBD was slightly higher, when compared to non-PBD patients, the present study revealed that the postoperative hospital stay in the PBD group was significantly shorter than that in the non-PBD group. This observation was probably correlated to the decrease in postoperative complications and faster recovery.…”
Section: Discussioncontrasting
confidence: 66%
“…The decrease in bilirubin levels also helps the body overcome the surgical stress. 27 Although the total length of hospital stay of patients with PBD was slightly higher, when compared to non-PBD patients, the present study revealed that the postoperative hospital stay in the PBD group was significantly shorter than that in the non-PBD group. This observation was probably correlated to the decrease in postoperative complications and faster recovery.…”
Section: Discussioncontrasting
confidence: 66%
“…There are metaanalyses showing positive results for PTBD as compared to ERCP for patients with malignant biliary obstruction. However, the results of these metaanalyses are limited due to significant heterogeneity across the studies and the limited data available specifically on the management of distal malignant biliary obstruction (117,118) . There fore, PTBD at this time could be considered as a suitable option to the endoscopic approach in cases of distal malignant tumors, particularly in selected centers with high expertise in percutaneous interventions.…”
Section: Malignant Biliary Stricturementioning
confidence: 99%
“…33 Nevertheless, there is still controversy in this area as a separate meta-analysis found no difference in technical success rates, leading some to argue that the evidence is quite heterogeneous. 34 When comparing the different types of endoscopic approaches, the use of EUS-BD has been reserved for patients that have failed ERCP. There are a variety of reasons to support this, including the novelty of EUS-BD, the lack of widespread availability and expertise, and until recently, the lack of high-quality evidence on its efficacy.…”
Section: Comparisonmentioning
confidence: 99%